Rückschritte, Irrwege - Simon Godart (Recherches Germaniques)
Alongside his essay on Charles Baudelaire, Walter Benjamin published a text by Carl Gustav Jochmann in the Zeitschrift für Sozialforschung in 1939, « The Regressions of Poetry », in a strongly abbreviated version and accompanied by an introduction. My paper shows how this antiromantic literary history of Jochmann on the regression of poetic writing served as a model for Benjamin, motivating the edition of the text. His approach towards literary history becomes, in Benjamin’s reading, the model for a criticism of the past, an omnipresent idea in his later writings.